2002
DOI: 10.2466/pr0.2002.90.2.477
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concept and Violent Delinquency in Urban African-American Adolescent Males

Abstract: African-American adolescent males experience a disproportionate rate of victimization associated with and arrest for violent crime. This study examined the between self-concept and violent delinquency within a group of 155 urban African-American adolescent males. Walter Reckless's 1967 containment theory, which suggest that a positive self-concept will insulate a juvenile from delinquency and crime, served as the theoretical frame of reference. The participants included 155 African-American males aged 13 to 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Engaging in delinquency may also be a more general marker for difficulties in forming personal identity, a struggle which has been related to poorer adjustment in general (e.g., Meeus et al 2012 ). Delinquency has been theorized to be a way of dealing with a negative self-concept (Levy 1997 ), and a more positive self-concept has been linked to lower assaultive delinquency (Bynum and Weiner 2002 ). Based on research on identity and delinquency as well as the link between self-concept clarity and identity, self-concept clarity was expected to be negatively related to delinquency.…”
Section: Introductionmentioning
confidence: 99%
“…Engaging in delinquency may also be a more general marker for difficulties in forming personal identity, a struggle which has been related to poorer adjustment in general (e.g., Meeus et al 2012 ). Delinquency has been theorized to be a way of dealing with a negative self-concept (Levy 1997 ), and a more positive self-concept has been linked to lower assaultive delinquency (Bynum and Weiner 2002 ). Based on research on identity and delinquency as well as the link between self-concept clarity and identity, self-concept clarity was expected to be negatively related to delinquency.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted in the general education system (i.e., regular education classes and resource rooms) have demonstrated that adolescents with CD frequently present a low level of global self-esteem (Al-Talib & Griffi n, 1994;Barry, Frick, & Killian, 2003;Bynum & Weiner, 2002;Donnelan, Trzesniewski, Robins, Moffi tt, & Capi, 2005;Harter, Whitesell, & Junkin, 1998;Hay, 2000;Levy 1997Levy , 2001Sprott & Doob, 2000) and a similar level of global physical self-perceptions (Al-Talib & Griffi n, 1994;Hay, 2000;Levy, 1997Levy, , 2001 in comparison with normally achieving (NA) students. However, other studies explain that when adolescents with CD are schooled in a segregated education system (i.e., segregated classes in a specialized establishment) they tended to present lower levels of global self-esteem (Al-Talib & Griffi n, 1994;Evans, Levy, Sullenberger, & Vyas, 1991;Levy 1997Levy , 2001Maïano, Ninot, Bilard, & Albernhe, 2002;Sweitzer, 2005), global physical self-perceptions (Al-Talib & Griffi n, 1994;Levy 1997Levy , 2001Maïano et al, 2002;Sweitzer, 2005), and perceived physical condition and sport competence (Maïano et al, 2002) than NA students.…”
Section: Physical Self-concept and Adolescents With CDmentioning
confidence: 99%
“…There is substantial theoretical and empirical evidence to suggest that self-concept, or the association of self with a trait, is a fundamental factor related to engagement in criminal behaviour (Bacchini et al, 2017;Bynum & Weiner, 2002;Nunes et al, 2013;Simourd & Olver, 2002). More specifically, research examining self-concept has revealed that maintaining an aggressive self-concept is associated with aggressive traits and aggressive behaviour .…”
Section: Purpose and Conclusionmentioning
confidence: 99%